2011
DOI: 10.1093/geronb/gbr062
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Positive and Negative Age Stereotype Priming Effects on Behavior Among Older Adults

Abstract: Findings show that negative age stereotyping has a much stronger influence on important behavioral outcomes among older adults than does positive age stereotyping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
191
1
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(219 citation statements)
references
References 19 publications
15
191
1
12
Order By: Relevance
“…Within these frameworks, experimental studies involving stereotype activation have shown that both implicit (subtle/subconscious) and explicit (conscious) negative age stereotyping can have similar detrimental effects on the performance of older people in physical and mental tasks [16,17]. In 2012, Meisner [17] conducted a meta-analysis to compare the strength of positive versus negative age stereotyping effects on behavioral outcomes in older adults.…”
Section: How Stereotypes Work To Affect Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Within these frameworks, experimental studies involving stereotype activation have shown that both implicit (subtle/subconscious) and explicit (conscious) negative age stereotyping can have similar detrimental effects on the performance of older people in physical and mental tasks [16,17]. In 2012, Meisner [17] conducted a meta-analysis to compare the strength of positive versus negative age stereotyping effects on behavioral outcomes in older adults.…”
Section: How Stereotypes Work To Affect Healthmentioning
confidence: 99%
“…In 2012, Meisner [17] conducted a meta-analysis to compare the strength of positive versus negative age stereotyping effects on behavioral outcomes in older adults. He found, regardless of the type of prime awareness, discipline of study, method, or participant group, that negative age priming elicited a stronger effect (of almost three times larger) on the performance of older individuals during physical and mental tasks than did positive age priming [17]. However, a major limitation of this analysis was that most of the studies included in the review came from Levy's lab.…”
Section: How Stereotypes Work To Affect Healthmentioning
confidence: 99%
“…Stereotypes concerning aging have been shown to predict health, illness, and other behavioral outcomes in later life. Positive age stereotypes are associated with positive effects, whereas negative age stereotypes are related to negative effects (Meisner, 2012). Although there is a tendency for a more positive image and greater evidence supporting that older adults can contribute to society in many different ways, some pervasive misconceptions, attitudes, and stereotypes still prevail (Dionigi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…La literatura describe una serie de estereotipos sociales [13][14][15][16] , en donde los autores Arnold-Cathalifaud 11 y Barrett 12 recogieron las opiniones de jóvenes con respecto a los AM, basándose el primero, en la opinión de jóvenes chilenos y el segundo en jóvenes estadounidenses.…”
Section: Estereotipos Que Deben Enfrentar Los Adultos Mayoresunclassified